Tax expenditures in the system agriculture taxation system in Poland and selected EU countries - Staniszewski, Jakub (Progress in Economic Sciences; No 2 (2015): Progress in Economic SciencesDO - 10.14595/PES/02/008, 2015)
Article raises the issue of the agriculture specificity in the context of tax system. It presents the arguments for intervention in the agricultural sector, using a variety of tools, including tax policy. Preferential taxation of agricultural activity is an example of the tax expenditure. Various preferences are used in most EU countries. A specific example is Poland, where farmers are completely exempt from paying income tax, which is the basis of agriculture taxation in other EU countries. Although, a number of arguments for and against the use of tax expenditures can be brought, it cannot be forgotten that the primary goal taxation is to provide incomes to the budget. The situation when the stimulative function of the taxes starts to dominate the fiscal one, especially in the face of pressure from interest groups, is undesirable.